2017
DOI: 10.1007/s13201-017-0578-5
|View full text |Cite
|
Sign up to set email alerts
|

Modification of thin-film polyamide membrane with multi-walled carbon nanotubes by interfacial polymerization

Abstract: Polyamide thin-film composite (TFC) was fabricated on polysulfone (PS-20) base by interfacial polymerization of aqueous m-phenylenediamine (MPD) solution and 1,3,5-benzenetricarbonyl trichloride (TMC) in hexane organic solution. Multi-wall carbon nanotubes (MWCNT) were carboxylated by heating MWCNT powder in a mixture of HNO 3 and H 2 SO 4 (1:3 v/v) at 70°C under constant sonication for different periods. Polyamide nanocomposites were prepared by incorporating MWCNT and the carboxylated MWCNT (MWCNT-COOH) at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…3), demonstrating that more COOH groups are introduced by the acid oxidation. 39 Additionally, the peaks at 1624 cm À1 , 1383 cm À1 and 1122 cm À1 shis to 1633 cm À1 , 1384 cm À1 , and 1125 cm À1 , respectively, it also reveals the structure changes of MWCNT upon carboxylation.…”
Section: Acid Oxidation Of Mwcntmentioning
confidence: 89%
See 1 more Smart Citation
“…3), demonstrating that more COOH groups are introduced by the acid oxidation. 39 Additionally, the peaks at 1624 cm À1 , 1383 cm À1 and 1122 cm À1 shis to 1633 cm À1 , 1384 cm À1 , and 1125 cm À1 , respectively, it also reveals the structure changes of MWCNT upon carboxylation.…”
Section: Acid Oxidation Of Mwcntmentioning
confidence: 89%
“…The FTIR spectrum of pristine MWCNT displays not only C]C peaks at 1383 cm À1 and 1122 cm À1 , but also many other small peaks, namely, O-H peak at 3434 cm À1 , C-H peaks at 2925 cm À1 and 2850 cm À1 , and C]O peak at 1624 cm À1 , indicating the presence of hydroxyl and carboxyl groups. [38][39][40] These hydroxyl and carboxyl groups in as-received MWCNT could be attributed to the purication process by the manufacturer. 41 On acid treatment, two characteristic peaks of the carboxyl group are seen at 1705 cm À1 and 1579 cm À1 , respectively (as shown in the dashed circle of Fig.…”
Section: Acid Oxidation Of Mwcntmentioning
confidence: 99%
“…[17][18][19][20] In this purpose, the functionalized CNT was embedded in the polyamide thin lm during interfacial polymerization or additional coating. [22][23][24] Nevertheless, few studies have described carbon nanotubes employed in the TFC membrane for PRO process. In this study, the CNTs incorporated in the support layer of TFN membranes was analyzed to determine their anti-biofouling ability in the PRO mode for potential applications of the PRO process.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the tubular shape of MWCNT nanoparticles can offer fast transport for passing water molecules through, thereby facilitating mass transfer in the process of membrane formation which gives the membrane a better pore structure. [13,14] Choi et al fabricated MCWNT/PSf nanocomposite membranes using the phase inversion method. They reported that the addition of MWCNT nanoparticles enhanced the filtration performance of the PSf membranes by altering morphology and controlling the hydrophilicity of the membrane surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the Van der Waals interactions among the tubes, the uniform dispersion of CNT nanoparticles in a polymer matrix is very difficult, which greatly limits their application. [14,16] To overcome the obstacles to CNT application, some functionalized CNT such as carboxylic acid-functionalized CNT, sulfonated CNT and phosphonated CNT have been subjected to the chemical modification approach followed by sonication and, therefore, have been used to facilitate the dispersion of CNT nanoparticles. [13,16] For example, Sianipar et al improved the dispersion of MWCNT to provide an antifouling behavior by coating CNT with polydopamine (Pdop).…”
Section: Introductionmentioning
confidence: 99%